Kursi Roda Elektrik dengan Kendali Gestur Kepala - Tiar Prilian; Iyus Rusmana; Trie Handayani (Institut Teknologi Dirgantara Adisutjipto, 2021)
A wheelchair is a tool that can be used to mobilize patients who experience paralysis, especially paralysis in the legs, so they can move from one place to another independently. An electric wheelchair is a type of wheelchair that can be controlled by a patient without having to be controlled by another person. The design of this tool utilizes an ADXL335 accelerometer sensor mounted on the patient's head as a determinant of the direction of wheelchair movement, BTS7960 as a DC motor driver, a motor wiper as the main drive for a wheelchair, and the Atmega328P microcontroller as an input and output processor. Gestures of the patient's head (looking down, looking up, head tilted to the right, tilting left) will produce a different voltage output which will be processed by Atmega328P as a determinant of the direction of motion which will be sent to the BTS790 driver to drive the wiper motor as the main driver of the wheelchair. The method of testing and measurement carried out by testing the response of the ADXL335 accelerometer sensor, with the test results of the ADXL335 accelerometer sensor having an accuracy of determining the direction of motion of 100%. The results of head gesture control testing the average wheelchair speed of 2.3 km / hour with a patient weight of 40-60 kg, and the test results of battery endurance in a wheelchair of 5.07 hours with a patient weight of 40-70 kg with a 12V18Ah battery.